Diversity of boreal small species of Cortinarius subgenus Telamonia with Salix - Kokkonen Katri (Societas Mycologica Fennica, 2022)
This work presents the genetic and morphological diversity of small Cortinarius subgenus Telamonia species found from moist Salix thickets in Finland. The boreal fungi were compared with several type and other specimens from the alpine zone or similar habitats from the temperate zone. The boreal and alpine zones had many common species: nearly all boreal species grew in the alpine zone with dwarf Salix. The species often had wide distributions, extending to North America. The genetic analyses consisted of ITS and RPB2 sequences. Both genetic and morphological variation was high. The species formed complexes, where the boundaries among species were often obscure. Very close sibling species were delimited based on differences at the same sites. Twenty-three boreal species were recognized. Four of them are described here as new: C. paulus and C. paululus as sibling species to C. pauperculus J.Favre, C. rusticelloides as a sibling species to C. rusticellus J.Favre, and C. vienoi as a sibling species to C. perzonatus Reumaux. Cortinarius sagarum, a sibling species to C. comatus J.Favre and C. vulpicolor M.M.Moser & McKnight, is described as new from arctic-alpine zones.